EXISTENTIAL DIMENSION OF THE INDIVIDUAL LIFESTYLE - Perevozchikova, Larisa; Radugin, Alexey; Radugina, Olga (Revista Inclusiones, 2020)
The study of individual lifestyles in today’s world is related to the ongoing transformation of the conditions of existence of members of society, which brings about changes in ways of organizing life practices related to the transition of society towards a new stage of civilizational development, i.e. the information society. Object: The aim of the paper is to reveal the existential dimension of lifestyles and its crucial role in the individual’s destiny, based on research into the main individual behavior patterns in various sociocultural settings. A lifestyle acts as a psychological, physiological and sociocultural bond of the human life and ensures its integrity. From a social perspective, a lifestyle, which refers to a comprehensive system of deep-rooted life practices, acts as the main regulator of the individual’s entire life. As a structure organizing the individual’s activities, a lifestyle takes on existential significance for the individual. Methods: An analysis of the lifestyle as an existential phenomenon should be based on the writings of Edmund Husserl and Alfred Schutz, the German philosophers who explored the ‘living world’ as well as on the existentialist principles developed by Jean-Paul Sartre and Martin Heidegger, among others.